Supplement to the genus Pseudokuzicus Gorochov, 1993 (Orthoptera: Tettigoniidae: Meconematinae) with one new species from China - Lv, Wenqing; Shi, Fuming; Chang, Yanlin (Zootaxa, 2024)
This paper describes one new species of the genus Pseudokuzicus Gorochov, 1993 from Guangxi, China, i.e. Pseudokuzicus (Similkuzicus) multispinus sp. nov., which is similar to Pseudokuzicus (Similkuzicus) quadridentatus Shi, Mao & Chang, 2007. Morphological photographs of the new species, supplementary description and photographs of male genitalia of Pseudokuzicus (Similkuzicus) quadridentatus Shi, Mao & Chang, 2007 are provided.